Validity and reliability assessment of the Brazilian version of the Faces Pain Scale-Revised - Charry,Claudia L. E. (2014)
The Faces Pain Scale-Revised (FPS-R) is among the most commonly used measures of pain intensity in clinical and research settings. Little evidence exists about the Brazilian version of this scale. The purpose of the present study was to examine the validity and reliability of the Brazilian version of the FPS-R. The sample comprised 214 children, 6 to 10 years of age. In the first phase of the study, the children ranked the faces of the FPS-R according to pain intensity, and the faces were presented in all possible pair combinations (content validity). All six faces were correctly ranked by 47% of the younger children (6 to 7 years old) and 52% of the older children (8 to 10 years old). With regard to paired combinations, all of the pairs were correctly placed by 63% of the younger children and 67% of the older children. In the second phase, the children rated recalled experiences of pain using both the Brazilian version of the FPS-R and Coloured Analogue Scale (CAS; convergent validity). The children were retested 4 weeks later (test-retest reliability). The degree of agreement between the FPS-R and CAS was moderate, with a Kendall's tau-b (τ) of .49 (p < .01). The test-retest reliability coefficient was τ = .52 (p < .01). This study provides evidence of the validity and reliability of the FPS-R as a pain intensity measurement for use in Brazilian samples.